Pengaruh Distributed Practice Terhadap Tembakan Bebas Atlet Bolabasket Junior Putra Klub Galaxy Kota Padang Panjang - Mariati, Sari; Syahara, Sayuti; Barlian, Eri (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
This study is an experimental study that aims to determine the effect of distributed practice on free shots of junior men's basketball athletes of the Galaxy Club of Padang Panjang City. The research population is 47 male basketball athletes of the Galaxy Kota Panjang club, because based on the needs of this study, junior male athletes who are actively practicing, the sample used is 20 people, with a purposive sampling technique. After the pre-test, all samples were given distributed practice exercises. The implementation of the research consisted of 16 meetings; in a week, the exercises were carried out as many as 4 times. The results of the pre-tests recorded are the results of free shots that come in after 10 shot attempts. Based on the data analysis, it can be concluded that there is no significant effect of distributed practice on free shots, which is an average of 4.20 (pretest) to 4.50 in the post test, where tcount = 0.67 <ttable = 2.26.